Dysregulated Prefrontal Cortex Inhibition in Prepubescent and Adolescent Fragile X Mouse Model - Kramvis, Ioannis; van Westen, Rhodé; Lammertse, Hanna C. A.; Riga, Danai; Heistek, Tim S.; Loebel, Alex; Spijker, Sabine; Mansvelder, Huibert D.; Meredith, Rhiannon M. (Frontiers in Molecular Neuroscience, 2020)
Changes in excitation and inhibition are associated with the pathobiology of neurodevelopmental disorders of intellectual disability and autism, and are widely described in Fragile X syndrome (FXS). In the prefrontal cortex (PFC), essential for cognitive processing, excitatory connectivity and plasticity is found altered in the FXS mouse model, however, little is known about the state of inhibition. To that end, we investigated GABAergic signalling in the Fragile X Mental Retardation 1 knock out (Fmr1-KO) mouse medial PFC (mPFC). We report changes at the molecular, and functional levels of inhibition at three (prepubescence) and six (adolescence) postnatal weeks. Functional changes were most prominent during early postnatal development, resulting in stronger inhibition, through increased synaptic inhibitory drive and amplitude, and reduction of inhibitory short-term synaptic depression. Noise analysis of prepubescent post-synaptic currents, demonstrated increased number of receptors opening during peak current in Fmr1-KO inhibitory synapses. During adolescence amplitudes and plasticity changes normalized, however inhibitory drive was now reduced in Fmr1-KO, while synaptic kinetics were prolonged. Finally, adolescent GABAA receptor subunit α2 and GABAB receptor subtype B1 expression levels were different in Fmr1-KOs than WT littermate controls. Together these results extend the degree of synaptic GABAergic alterations in FXS, now to the mPFC of Fmr1-KO mice, a behaviourally relevant brain region in neurodevelopmental disorder pathology.